2021
DOI: 10.3389/fpls.2021.634091
|View full text |Cite
|
Sign up to set email alerts
|

The Candidate Photoperiod Gene MtFE Promotes Growth and Flowering in Medicago truncatula

Abstract: Flowering time influences the yield and productivity of legume crops. Medicago truncatula is a reference temperate legume that, like the winter annual Arabidopsis thaliana, shows accelerated flowering in response to vernalization (extended cold) and long-day (LD) photoperiods (VLD). However, unlike A. thaliana, M. truncatula appears to lack functional homologs of core flowering time regulators CONSTANS (CO) and FLOWERING LOCUS C (FLC) which act upstream of the mobile florigen FLOWERING LOCUS T (FT). Medicago t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Extensive research revealed that the flowering-related genes are largely conserved between Arabidopsis and legumes [ 42 , 44 , 45 , 49 , 53 , 54 , 55 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. However, the legumes generally lack any FLC orthologs, except for soybean, a vernalization-independent species, which retained one FLC copy in its paleopolyploid genome [ 42 , 98 , 99 ].…”
Section: The Mechanism Of Cold–induced Flowering In Arabido...mentioning
confidence: 99%
“…Extensive research revealed that the flowering-related genes are largely conserved between Arabidopsis and legumes [ 42 , 44 , 45 , 49 , 53 , 54 , 55 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. However, the legumes generally lack any FLC orthologs, except for soybean, a vernalization-independent species, which retained one FLC copy in its paleopolyploid genome [ 42 , 98 , 99 ].…”
Section: The Mechanism Of Cold–induced Flowering In Arabido...mentioning
confidence: 99%
“…Medicago has six FT -like genes, of which MtFTa1 responds to long exposure to cold (vernalization) and is rapidly up-regulated in leaves in response to the LD photoperiod [ 8 , 9 ]. Integrator genes that regulate photoperiodic flowering genes have been discovered in Medicago [ 10 , 11 , 12 ]; however, it is still not clear which component/s is/are key for translating light inputs into the circadian clock to provide photoperiod-specific regulation of flowering. In Pisum sativum (pea), orthologs of the clock genes ELF3, LUX, ELF4 all contribute to the repression of FT family gene expression and flowering under short days (SD) [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further research revealed that the CiFE‐CiFT complex binds to the citrus LEAFY ( CiLFY ) promoter and activates its expression. In Arabidopsis and Medicago truncatula , FE promotes flowering through the transcriptional activation of FT (Abe et al, 2015; Thomson et al, 2021). Thus, our results provide novel insights into the relationship between environmental stress factors and flowering through the regulation of CiNF‐YA1 in citrus plants.…”
Section: Introductionmentioning
confidence: 99%